Study on the Anti-Photocorrosion Mechanism of Novel Self-Assembled Spherical Cu2O/FePO4 Z-Scheme Heterojunctions - Kuo Zhang; Xiufei Zhao; Hang Qian; Lihong Chen; Biyu Wu; Xiao Yang; Haonan Zou; Yujiao Hu; Feng Chen; Borong Liao; Hu Zhou; Lei Zhang; et al. (Reactions)
Cu2O, a narrow-bandgap semiconductor with visible light absorption capabilities, faces limitations in photocatalytic applications due to photocorrosion from hole self-oxidation and insufficient light absorption. In this work, a series of novel spherical Cu2O/FePO4 Z-scheme heterojunctions were successfully synthesized via self-assembly to overcome these challenges. The photocurrent, electrical impedance spectroscopy (EIS), and photoluminescence (PL) tests showed that Cu2O/1.5FePO4 (CF1.5) had excellent electron hole separation efficiency. Subsequently, photocatalytic degradation was utilized as a probing technique to further confirm the above conclusions, with the kinetic reaction constants of CF1.5 being 2.46 and 11.23 times higher than those of Cu2O and FePO4, respectively. After five cycles of experiments and XPS analysis, it was found that the content of Cu(I) in CF1.5 did not significantly decrease after the reaction, indicating that it has superior anti-photocorrosion performance compared to single Cu2O, which is also due to the establishment of a Z-scheme heterojunction. Systematic studies using radical scavenging experiments and ESR tests identified ·OH and ·O2− as the main active species involved in photocatalysis. The formation of a Z-scheme heterojunction not only enhances the photocatalytic activity of the CF1.5 composite but also effectively suppresses the photocorrosion of Cu2O, thereby offering a promising approach for enhancing anti-photocorrosion of Cu2O.